THE SMART CITY HOSPITALITY SYSTEM: TO CREATE A FOUNDATION FOR COLLECTIVE OVER TOURISM REFLECTIONS THAT HELP DESTINATION PLANNING - Sitikantha Mishra , Bibhuti B Pradhan , Ansuman Samal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper introduces the Smart City Hospitality Framework, which could serve as the basis for a destination-design-driven approach to governance of urban tourism and addressing over tourism issues. The aim of this conceptual structure is to encourage collective (informed) reflections on over tourism and urban tourism growth that could help system analyses, issue structuring and the creation of transformation strategies and frameworks in the sense of transforming urban tourism into a strategic environment that commends putting in motion a sustainability change at city level. It fuses the elements of sustainable growth (environmentally friendly and equitable economic development) and community hospitality (the ex- tent of which the community serves as a good ’host’ for all its ’guests,’ including residents and businesses). Resilience rests at its heart to highlight the spatial implications and interdependencies of these dimensions. A brief overview of (experiences with) intense game-playing sessions that implement its theory in six European cities is presented to demonstrate how this concept will serve as the basis for the efforts of destination design in practice.